A Formação de professores nas tramas do virtual - Súnega, Paula Beatriz Camargo (2016)
This study aims to reflect on the cultural and aesthetics formation of teacher, and how they act as a co-author in the virtual environment. The reflection permeates on topics such as: The Information Age and the challenges of the teacher in the twenty-first century; teacher professional development and the multiple personal identities; the importance of cultural repertoire for teaching practice and the role of the teacher as co-author in the informational network. In addition to the theoretical reflections were conducted two focus groups with the participation of teachers with different graduations and working in various levels of education to discuss the presented topics. It was proposed to create a website for the teacher to sail and collaborate with posts on many cultural artifacts. For the construction of the content for the site, it developed a “daily creation”, which is the search information storage from multiple sources, such as academic papers, songs, websites, magazines, comics, blogs, books, photographs, advertisements, finally everything that can increase imagination and serve for the production of content. Data analysis of the focus group showed that teachers recognize the varied cultural repertoire makes for a good professional aplomb, but cannot actively participate in the local culture. It was also found that the teacher has difficulty manipulating information technology and communication and therefore, distance themselves from an active production network. The focus group contributed to building a website and posts on cultural artifacts. Production can be accessed at www.digitaldoprofessor.com.